Current scenario of milk production in the North-eastern states of India: Challenges and mitigation strategies to address milk shortfall - MILI, BHABESH; DUTTA, HARIPRIYA (The Indian Journal of Animal Sciences, 2024)
Livestock husbandry is an inseparable part of the rural economy of Northeastern (NE) states. The local market demand for milk is expanding, indicating the need for intervention in dairy development. This study focussed on the current status of milk production and the challenges faced in improving dairy production. Secondary data were collected from the Livestock Census (2019) and Basic Animal Husbandry Statistics (2019 and 2023), Government of India. The results revealed that total milk production in the NE states was 1608.04 thousand tonnes in 2022-23, accounting for only 0.70% of the country’s milk production during the same year. The compounded annual growth rate (CAGR) of milk in the NE states was 1.59%, significantly lower than that in India (3.83%). Among NE states, Tripura registered the highest CAGR in milk production (5.2%), followed by Meghalaya (3.51%), Assam (2.42%), and Sikkim (0.01%). The remaining NE states experienced negative growth. Except for Sikkim, the per capita milk availability in the NE states was considerably lower than that in India. Additionally, there were significant gaps in meeting milk requirements according to the ICMR recommendations in these states. Mizoram had the highest shortfall of milk (-81.78%), followed by Nagaland (-79.54%), Manipur (-79.45%), Meghalaya (-74.26%), Arunachal Pradesh (-73.13%), Assam (-74.02%), and Tripura (-48.85%) during 2022-Sikkim had a surplus milk production of 15.70%. Addressing this shortfall represents substantial market potential opportunity to expand the milk market across all NE states, thereby enhancing livelihoods, food security, and the socio-economic status of millions of people.